In Vitro Antimicrobial Activity of Ethanolic Extract of Polish Propolis against Biofilm Forming Staphylococcus epidermidis Strains. (10th April 2013) - Wojtyczka, Robert D.; Kępa, Małgorzata; Idzik, Danuta; Kubina, Robert; Kabała-Dzik, Agata; Dziedzic, Arkadiusz; Wąsik, Tomasz J.
Abstract : The aim of the presented study was to examine the antimicrobial activity of ethanol extract of Polish propolis (EEPP) against biofilm-forming CoNS strains in vitro . Our results revealed that EEPP displayed varying degrees of activity against CoNS with MIC values ranging from 1.56 to 0.78 mg/mL. The average MIC was 1.13 ± 0.39 mg/mL while calculated MIC50 and MIC90 values were 0.78 mg/mL and 1.56 mg/mL, respectively. The biofilm formation ability by all tested S. epidermidis strains was inhibited at EEPP concentrations ranging from 0.39 to 1.56 mg/mL. The degree of reduction of AlamarBlue was directly associated with the proliferation of S. epidermidis strains. The increased proliferation of S. epidermidis strains was observed after 12 and 24 hours of incubation in the presence of EEPP concentrations ranging from 0.025 to 0.39 mg/mL. These results suggest that antimicrobial activities of EEPP against S. epidermidis expressed as the reduction of bacterial growth, reduction of biofilm formation ability, and the intensity of proliferation were significantly affected by incubation time and EEPP concentration used as well as the interactions between these factors.